APPLICATION OF E-TRANSPORT TROUGHT DESIGNING TIKETING INFORMATION SYSTEM USING DIAGRAM ACTIVITIES - Andri Sihata Sitanggang (Bakti Nusantara Institute, 2018)
E-Transport is a form of service / facility provided to the public in the field of transfer using electronic media. E-transport itself can be in the form of a guide to route use services on transportation, road monitoring services to transportation users in real time, services such as booking tickets for a transportation service provider, services such as gps guiding vehicles for travel and other security services. One of the services that is currently developing in the community is travel services, where travel services provide transportation services based on the destination location. In the city of Bandung itself travel services have been very much, but the problem that occurs is how to provide maximum service to the community, especially in booking tickets, not only fixated on the convenience of transportation services, but travel booking service services are also very important . Travel booking services should have been greatly paid attention to by travel service providers, so that people are accustomed to and believe in using travel services rather than having to use private vehicles so as to reduce the amount of transportation in the city of Bandung. So this research is based on improving the quality of service providers in the city of Bandung.